SINTESIS DAN STUDI STABILITAS NANOPARTIKEL PERAK TERTUDUNG ASAM SALISILAT - Rizky Noviani Ridwan; Gusrizal Gusrizal; Nurlina Nurlina; Sri Juari Santosa (Indonesian Journal of Pure and Applied Chemistry, 2018)
Silver nanoparticles capped with salicylic acid have been synthesized by reduction of silver nitrate with salicylic acid without additional capping agent. In the formation of silver nanoparticles, the solution of silver nitrate was first mixed with the pH 11 salicylic acid solutions at a mole ratio of 1:40. The mixture was heated for 45 minutes in a boiling water bath. The formation of silver nanoparticles was indicated by the appearance of yellow color and monitored using UV-Vis spectrophotometer. The maximum peak of resulted silver nanoparticles appeared in the range of 410-420 nm with the average size of particles was 66±28 nm. Stability test over a period of 16 weeks showed that silver nanoparticles capped with salicylic acid were stable. The results of stability test show that salicylic acid simultaneously act as reducing as well as capping agent in the formation of silver nanoparticles.